How Self Management and Achievement Motivation Contribute to Student Discipline - Arsih, Salsabila; Mudjiran, Mudjiran; Nirvana, Herman; Sukma, Dina (Journal of Educational, Health and Community Psychology, 2025)
The educational process needs to be guided by clear rules and regulations so that the learning atmosphere remains orderly and educational goals can be achieved optimally. Discipline enables students to direct and control their behavior in accordance with school expectations. This study employed a quantitative approach with a descriptive correlational design. The sample consisted of 250 students in Grades VII, VIII, and IX at SMP Pembangunan Laboratorium UNP, selected using proportional random sampling. Research instruments included self-management, achievement motivation, and student discipline scales based on a Likert response format. Data were analyzed using descriptive statistics and multiple regression analysis. The results indicated a significant relationship between self-management and achievement motivation and student discipline, with both predictors jointly accounting for 25.4% of the variance in discipline. These findings can be used as input for designing guidance and counseling service programs at SMP Pembangunan Laboratorium UNP.